Preferential Solvation of Indomethacin in Some Aqueous Co-Solvent Mixtures (2023)
The preferential solvation parameters for indomethacin (IMC) in ethanol (EtOH) + water and propylene glycol (PG) + water binary mixtures were obtained from their thermodynamic properties by means of the inverse Kirkwood–Buff integrals (IKBI) and the quasi-lattice quasi-chemical (QLQC) methods. According to IKBI method, the preferential solvation parameter by co-solvents, (dx1,3), is negative in the water-rich mixtures of both binary systems but positive in the other compositions at temperatures of 293.15, 303.15, and 313.15 K. It is conjecturable that in water-rich mixtures the hydrophobic hydration around the aromatic rings and methyl groups of the drug plays a relevant role in the solvation. The higher drug solvation by co-solvent in mixtures of similar solvent proportion and in co-solvent-rich mixtures could be due mainly to polarity effects. Here IMC would be acting as a Lewis acid with the EtOH or PG molecules because these co-solvents are more basic than water. © 2016, Copyright © Taylor & Francis Group, LLC.